Implementasi Ontologi untuk Personalisasi Pembelajaran Online pada Mata Kuliah Jaringan Komputer - Suteja, Bernard Renaldy (Zenit, 2015)
Cognitive aspects differ among students. Online learning system today does not take part in any aspects of individual students, ignoring the differences in specific needs or personalization of thecognitive experience. This research carried out on a personalized approach to online learning is based on an ontology. A model is developed to further student’s integration with the ontology, thusallowing the personalization system to guide the learning process of students. The models are developed to monitor the students’ progress, so that it can update the content knowledge of studentsand determine the next content to be taught.Keywords: : online learning, personalization, ontology